Why organisations adopt family-friendly policy : a case of corporate childcare centre in a manufacturing company - Omar, Zoharah (2009)
Using a case study approach, this study seeks to examine the form and structure of a childcare centre at the workplace, and to explore the reasons organisations set-up a childcare centre at the workplace. This study was conducted in a private manufacturing company using qualitative methodology. Data were collected through in-depth interview and document analysis. Three theoretical perspectives, the institutional theory, the rational choice approach and the resource dependence theory, were used as a framework of analysis to explain reasons that drive the organisation to set-up up a childcare centre at the workplace. The findings of this paper revealed that the reasons for setting-up a childcare centre were to attract and retain employees, to reduce unplanned leave and absenteeism, and to increase productivity. Besides, the findings also suggest that organisation culture and the human resource professional are also important in influencing the organisation’s decision to set-up its corporate child care centre. The findings of this study have several theoretical and practical implications.